Empirical Evaluation of Financial Performance Differentials between Quoted and Unquoted Firms in Nigeria: Asset Base and Revenue as critical Determinants - Osirim, Monday; Wadike, Chile George (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2023)
There has been a long debate on what constitutes the financial performance of a firm. The thrust of this paper therefore was to determine the financial performance of quoted and unquoted firms in Nigeria using asset base and revenue as critical determinants. The study is hinged on the philosophy and perception that quoted firms performs better than unquoted firms. A sample of Eighteen (18) firms was selected, nine apiece for quoted and unquoted companies. The analysis of the firms covered a period of nine years from 2008 to 2017. Vital information from the selected firms’ audited financial reports for various years were collected and analyzed. A Panel data fixed effect was used to determine the financial performance of quoted and unquoted firms while a paired sample statistics test was used in comparing the mean difference of both firms. Empirical results indicate that asset base and revenue have positive impact on the financial performance of quoted firms while only revenue has a positive relationship with financial performance of unquoted firms. The study concludes that there is a difference in the financial performance of quoted and unquoted firms in Nigeria. This difference may have emanated from the fact that unquoted companies lack the financial muscle that could be garnered by quoted firms; thus necessitating the recommendations that the Nigerian Stock Exchange should review its listing requirements to accommodate unquoted companies intending to be quoted.